Exposure to cigarette promotions and smoking uptake in adolescents: evidence of a dose-response relation - Sargent, J. (BMJ Group, 2000)
OBJECTIVE—To assess whether a dose-response relation exists between the number of cigarette promotional items (CPIs) owned by an adolescent, and smoking behaviour. DESIGN AND SETTING—Voluntary, self administered survey of 1265 sixth through to 12th grade students (ages 10-19 years), representing 79-95% of all students attending five rural New Hampshire and Vermont public (state funded) schools in October 1996. The association between the number of CPIs owned by students and smoking behaviour was examined using multivariate regression methods. OUTCOME MEASURES—Adjusted odds of being a smoker (⩾ 100 cigarettes lifetime) and, among never and experimental smokers, adjusted cumulative odds of having higher levels on a smoking uptake index given the number of CPIs owned. RESULTS—One third of students owned a CPI (n = 406). Among owners, 211 owned one, 82 owned two, 57 owned three, 24 owned four, 23( )owned five, and 7 students owned six CPIs. The number of CPIs owned by students was not associated with grade in school but was significantly higher in males, those with poorer school performance, those who perceived high prevalence of peer smoking, and those with higher exposure to peer and family smoking. The more items a student owned, the greater the chances of being a smoker. For example, smoking prevalence was 11.2% for those not owning a CPI, 41.5% for those owning two, 58.5% for those owning four, and 71.4% for those owning six CPIs. The dose-response relation remained after controlling for confounding; compared with those who did not own a CPI, the likelihood of being a smoker was significantly higher for those who owned one CPI, with an adjusted odds ratio (OR) of 2.7 (95% confidence interval (CI) 1.7 to 4.1); OR was 3.4 (95% CI 1.9 to 5.9) for those owning two CPIs, and 8.4 (95% CI 5.0 to 14.2) for those owning three or more CPIs. After excluding smokers, there was a crude dose-response association between CPI ownership and higher rates of experimentation with cigarettes among sixth to ninth graders (ages 11-15 years) only (n = 543). After controlling for confounding influences, the dose-response relation remained, with the likelihood of being higher on the smoking uptake index rising with the number of CPIs owned: one CPI, adjusted cumulative OR 1.7 (95% CI 1.1 to 2.60); two CPIs, OR 2.5 (95% CI 1.2 to 5.1); and three or more CPIs, OR 4.8 (95% CI 1.9 to 12.2). CONCLUSIONS—This study offers evidence of a dose-response relation between the number of CPIs owned by adolescents and higher likelihood of experimental and established smoking. The dose-response relation persists after controlling for confounding influences. These data provide further support of a causal relation between tobacco promotional campaigns and smoking behaviour among adolescents.   Keywords: adolescents; epidemiology; tobacco marketing